Establishing an Efficient Genetic Manipulation System for Sulfated Echinocandin Producing Fungus Coleophoma empetri - Men, Ping; Wang, Min; Li, Jinda; Geng, Ce; Huang, Xuenian; Lu, Xuefeng (Frontiers in Microbiology, 2021)
Micafungin is an important echinocandin antifungal agent for the treatment of invasive fungal infections. In industry, micafungin is derived from the natural product FR901379, which is a non-ribosomal cyclic hexapeptide produced by the filamentous fungus Coleophoma empetri. The difficulty of genetic manipulation in C. empetri restricts the clarification of FR901379 biosynthetic mechanism. In this work, we developed an efficient genetic manipulation system in the industrial FR901379-producing strain C. empetri MEFC009. Firstly, a convenient protoplast-mediated transformation (PMT) method was developed. Secondly, with this transformation method, the essential genetic elements were verified. Selectable markers hph, neo, and nat can be used for the transformation, and promotors Ppgk, PgpdA, and PgpdAt are functional in C. empetri MEFC009. Thirdly, the frequency of homologous recombination was improved from 4% to 100% by deleting the ku80 gene, resulting in an excellent chassis cell for gene-targeting. Additionally, the advantage of this genetic manipulation system was demonstrated in the identification of the PKS responsible for the biosynthesis of DHN-melanin. This genetic manipulation system will be a useful platform for the research of FR901379 and further genome mining of secondary metabolites in C. empetri.